β-D-Galactose-Functionalized Pillar[5]arene With Interesting Planar-Chirality for Constructing Chiral Nanoparticles - Sun, Guangping; Pu, Liangtao; Pangannaya, Srikala; Xiao, Tangxin; Hu, Xiao-Yu; Jiang, Juli; Wang, Leyong (Frontiers in Chemistry, 2019)
Planar-chiral pillar[5]arenes bearing β-D-galactose substituents on both rims have been successfully synthesized and effectively separated by silica gel chromatography with a high yield. The obtained (pS)- and (pR)-β-D-galactose functionalized pillar[5]arenes ((pS)-GP5 and (pR)-GP5) exhibit the pS and pR planar chirality. Furthermore, (pS)-GP5 and (pR)-GP5 can not racemize according to dynamic 1H NMR and CD spectra. Notably, GP5 is able to capture a guest molecule (DNS-CPT) to form a host-guest supramolecular amphiphile, which can further self-assemble into chiral nanoparticles with the pS and pR planar chirality of (pS)-GP5 and (pR)-GP5 still being retained, suggesting GP5 could be as reliable chiral sources to transfer the pS and pR planar chirality.